Simulation of heat transfer performance of silicone-based insulation coatings. (3rd November 2022) - Wei, Li; Shen, Kun; Wei, Dongxu; Wang, Kai
In order to investigate the heat transfer properties and insulation effect of silica-based insulation coating in pipe insulation, an ANSYS workbench is used, in this research work, to establish a thermal insulation model for heat transport pipes. The simulation study is carried out for silicon-based insulation coating, aerogel, aluminium silicate fibre, calcium silicate board, and other insulation materials with different thicknesses, different insulation structures, and different pipeline temperatures to compare their insulation effects, and the simulation results are verified with the tests that are carried out on the actual thermal pipelines, which show that silicon-based insulation coatings have a better thermal insulation effect than aluminium silicate fibre and calcium silicate board under the same boundary conditions and thickness, silicon-based insulation coatings have a better thermal insulation effect when the temperature is higher than 300°C.